Analisis Pengelolaan Bantuan Operasional Sekolah (BOS) pada SD Negeri 1 Ulaweng di Desa Ulaweng Kecamatan Samaturu Kabupaten Kolaka - Laode Asrun; Yudi Agusman; Maulid Maulid (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
This study aims to determine the management of School Operational Assistance (BOS) at SDN 1 Ulaweng in Ulaweng Village, Samaturu District, Kolaka Regency. The research method used is descriptive qualitative technique. Research informants, namely, elements of the school supervisor teacher and elements of the community. The types and sources of data in the following research are using primary data and secondary data. The results show that the Management of School Operational Assistance (BOS) at SD Negeri 1 Ulaweng in Ulaweng Village, Samaturu District, Kolaka Regency is not good in its implementation, this can be seen from the principle of accountability. The principle of proportionality regarding the rights and obligations carried out by school principals through BOS funds is still not implemented. The principle of professionalism regarding personal interests and school interests is not good in implementing BOS management, the principle of openness regarding transparency and publication of the BOS Budget is not implemented properly and is not based on existing regulations. The principle of the financial examiner regarding the preparation of reports on the results of the use of funds accurately and in accordance with the funds being managed and the reporting is good.